2019
DOI: 10.1097/aln.0000000000002527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex and Body Language on Patient Perceptions of Anesthesiologists

Abstract: Editor’s Perspective What We Know about This Topic What This Article Tells Us That Is New Background Patient perception of physician competence is important. The role of body language and physician sex on patient perceptions has not been investigated. The authors hypothesized that patients perceive anesthesiologists displaying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 21 publications
5
24
2
Order By: Relevance
“…We previously investigated the effect of anesthesiologist sex and body language on patient perceptions of anesthesiologist confidence, intelligence, likelihood of choosing the anesthesiologist to care for their family member, and leadership abilities. 14 We found that actor anesthesiologists who demonstrated confident, high-power body language were more likely to be ranked as confident and intelligent, more likely to be chosen to care for one's family member, and more likely to be to be considered a leader. Patient ranking of these qualities was not affected by sex of the actor anesthesiologists.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 81%
See 1 more Smart Citation
“…We previously investigated the effect of anesthesiologist sex and body language on patient perceptions of anesthesiologist confidence, intelligence, likelihood of choosing the anesthesiologist to care for their family member, and leadership abilities. 14 We found that actor anesthesiologists who demonstrated confident, high-power body language were more likely to be ranked as confident and intelligent, more likely to be chosen to care for one's family member, and more likely to be to be considered a leader. Patient ranking of these qualities was not affected by sex of the actor anesthesiologists.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 81%
“…We previously demonstrated that patient perception is influenced by body language, with patients ranking actor anesthesiologists who display confident body language as more confident, more intelligent, and more like a leader, and preferentially choosing that anesthesiologist to care for their family member when compared with anesthesiologists displaying unconfident body language. 14 Body language is a modifiable factor, and anesthesiologists who have a tendency to display unconfident body language can potentially undergo training to adopt more confident body language in order to improve patient perceptions. In the current study, patients displayed clear preferences based on age and sex, despite controlling for the effects of body language.…”
Section: Educationmentioning
confidence: 99%
“…Clearly explaining the anesthesia plan has previously been show to important in to patients and improves anxiety [4]. While displaying confident and approachable body language is no doubt important, there are likely other areas which may be more important to focus on, especially for trainees who are trying to improve their interview and communication skills [2] [3].…”
Section: Discussionmentioning
confidence: 99%
“…They found that a 'female staff anaesthetist was challenged more often and with greater assertiveness and effectiveness' than a male staff anaesthetist. 21 Conversely, Forkin and colleagues 20 did not find evidence of discrimination based on the gender of the anaesthesiologists in a randomised study of 200 patients presenting for preoperative evaluation in a single centre. The participants in that study viewed four 90 s videos of male and female anaesthesiologists displaying different body language, and were then asked to provide their perception of the physician's abilities.…”
Section: Environmental Factors (Six Articles Identified)mentioning
confidence: 96%
“…Participants' perceptions were positively affected by confident body language but were not related to the gender of the anaesthesiologist. 20 PubMed: 17 EMBASE: 4 MEDLINE: 1…”
Section: Environmental Factors (Six Articles Identified)mentioning
confidence: 99%